Análisis de la amenaza de sequía y su impacto socio económico y ambiental en la parroquia Santa Fé, cantón Guaranda, provincia Bolívar. Periodo mayo-septiembre 2023 - Camacho Velasco, Viviana Lisbeth (2023)
The study carried out in the Santa Fe parish focused on investigating the threat of drought and its socioeconomic and environmental impact. Precipitation data from the NASA platform were used to calculate the Standardized Precipitation Index (SPI) and characterize meteorological drought in different periods. In addition, socioeconomic and environmental vulnerability was assessed through structured surveys and the calculation of the global aridity index. Quantitative research has allowed the generalization of results, providing control over the phenomena, and focusing on measurements and magnitudes, facilitating the comparison of the results that have been described in each of them. The results indicated that the Santa Fé parish experiences moderate and severe droughts in different periods, with SPI values that vary between -0.22 and -2.94. The annual global aridity index suggests that the area has a semi-arid Mediterranean-type climate, while the monthly global aridity index indicates a more humid climate zone. The vulnerability of the area ranges from high to very high, highlighting the need to develop strategies to reduce vulnerability and protect the population from the threat of drought. Keywords: Strategies, aridity, precipitation, Santa Fe.